Hospital mortality due to ischemic stroke in the city of Bacabal - MA between 2010 and 2021: Epidemiological study (Research, Society and Development, 2024)
Introduction: Ischemic stroke is one of the main cause of morbidity and mortality worldwide. In Bacabal – MA city, stroke also has a significant impact on Public Health, which urges the needed for preventive actions in the region. Aimes: analyze hospital mortality due ischemic stroke in Bacabal - MA city between 2010 and 2021, as well as to discuss the risk factors, treatment and prognosis of this pathology. Methodology: A secondary database study was carried out in PROADESS on the percentage of hospital deaths among hospitalizations of patients aged 45 years or older with a length of stay of up to 30 days, due to ischemic stroke, per 100 hospitalizations, by occurrence place, between 2010 and 2021. Results: The analysis revealed trends with obvious variations in mortality over these years. Demographic characteristics, such as the most susceptible age group, and comorbidities were frequently associated with fatal outcomes, as well as limitations in treatment and prognosis. Conclusion: understanding the problem in Bacabal - MA, as a basis for targeted Public Health strategies, can help in the allocation of medical resources and the implementation of preventive measures.